Ecolexicon of Medicinal Plants in the Local Knowledge System of the Batak Toba Community - Nehemia Anugrah Parasian; Tasnim Lubis (Tradition and Modernity of Humanity, 2025)
This study examines the ecolexicon of medicinal plants in the local knowledge system of the Toba Batak people, as part of an effort to preserve the regional language and culture. Using a qualitative ethnographic approach, data were collected through interviews and documentation of native speakers who have traditional knowledge of medicinal plants. The results of the study revealed 20 types of medicinal plants known and utilized by the Batak Toba people, consisting of three main categories: leaves, fruits, and rhizomes. Each plant has a local name that reflects the biological, ideological, and sociological aspects of the speaker community. This lexicon not only reflects the ecological relationship between humans and nature, but also stores cultural values, mythology, and traditional healing practices that are passed down from generation to generation. This study emphasizes the importance of ecolexicon documentation as a form of preserving local knowledge and revitalizing endangered regional languages.